Pengaruh Promosi dan Ulasan Pelanggan Terhadap Keputusan Pembelian Produk Pakaian di Tiktok Pada Generasi “Z” Ambon - Syenita Gracia Letwory; Ambarwati Soetiksno; Arthur Sitaniapessy (Pusat Riset dan Inovasi Nasional, 2025)
Online promotions and customer reviews are factors expected to improve purchasing decisions. This study aims to determine the influence of online promotions and customer reviews on purchasing decisions for fashion clothing products on TikTok Shop among Generation Z in Ambon City. A sample of 110 respondents was taken using probability sampling technique with simple random sampling approach. The method used in this study is multiple linear regression analysis method with SPSS 21 software, obtained regression equation Y = 0.866 + 0.289X1 + 0.542X2. From the results of the study, hypothesis one produces a